A Corpus Analysis of Proposals: A Description and Implications - Awab, Su'ad (Journal of Modern Languages, 2017)
This study is an investigation into the use of corpus analysis in teaching writing, in particular professional writing. It describes holy a grammatical analysis of text might be used in the preparation of teaching materials and in assisting students to learn independently. The study shows that the measure of success in professional writing depends largely on whether the finished product communicates with its intended audience. It also mentions that, the document, for example a proposal, has to have the ability to perusable in order to convince and ultimately be accepted by the community of readers it is targeted for. This is due to the nature of business where factors such as time and economy play very important roles in determining the success and continuity of a company.